Multiomics Assessment of Gene Expression in a Clinical Strain of CTX-M-15-Producing ST131 Escherichia coli - Pinto, Luís; Torres, Carmen; Gil, Concha; Nunes-Miranda, Júlio D.; Santos, Hugo M.; Borges, Vítor; Gomes, João P.; Silva, Catarina; Vieira, Luís; Pereira, José E.; Poeta, Patrícia; Igrejas, Gilberto (Frontiers in Microbiology, 2019)
Extended spectrum beta-lactamase (ESBL)-producing Escherichia coli strain C999 was isolated of a patient with urinary tract infection. Previous genotyping indicated that this strain presented a multidrug resistant phenotype and carried the genes of the ESBL CTX-M-15, in addition to those of TEM-1 and OXA-1 enzymes. The whole-cell proteome, and the membrane, cytoplasmic, periplasmic and extracellular sub-proteomes of C999 were obtained in this work by two-dimensional gel electrophoresis followed by fingerprint sequencing through matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. A total of 602 proteins were identified in the different cell fractions, several of which are related to stress response systems, cellular responses, and antibiotic and drug responses, consistent with the multidrug-resistance phenotype. In parallel, whole genome sequencing and RNA sequencing was done to identify which genes are present and expressed as well as quantifying transcript levels. The in silico prediction following WGS confirmed our strain as being O25:H4. The presence of proteins related to pathogenesis and virulence in a O25:H4-ST131 E. coli clone are evidence of the continued threat of antibiotic resistance in healthcare institutions. On a positive note, a multiomics approach can facilitate surveillance and more detailed characterization of virulent bacterial clones from hospital environments.